MODIFIKASI MEDIA TANAM TOMAT BELINJAN PADA BERBAGAI INTERVAL PEMBERIAN NUTRISI SISTEM FERTIGASI - Abdul Wahid; Gusti Rusmayadi; Dewi Erika Adriani (Universitas Lambung Mangkurat, 2022)
It is necessary to choose the right planting media for vegetable cultivation with a fertigation system. Modification of growing media at various intervals of nutrition can be recommended. The study aimed to 1) analyze the interaction effect of the modification of planting media at various intervals of nutrition on the growth and yield of belinjan tomatoes in the fertigation system, 2) analyze single the effect of each treatment, 3) determine the best combination of treatment. This research was conducted in a greenhouse by using a pot through the treatment of a Split Plot Design. The first factor as the main plot is the interval of nutrition (B) consisting of 3 levels: b1 (3 times a day), b2 (5 times a day), and b3 (7 times a day) and the second factor as a sub-plot is the modification of planting media (A) the ratio of burnt husks: manure: cocopeat the ratio consists of 4 levels: a0 (burnt husk), a1 (2:1:1), a2 (1:2:1), and a3 (1:1) 1:2). The results showed that there was an interaction effect of treatment on the main plot and sub-plots at intervals of nutrition and modification of planting media on the variable of Brix level of belinjan tomato. The single factor of modification of the planting media affected the average number of fruits per bunch, the relative growth rate of 59-73 days after planting and the root shoots ratio. Combination of treatment 7 times per day of the interval level of nutrition with 100% of the burnt husk media resulted in tomato Brix levels at an average level of (5.70) better than other combinations.